Determination of Physical Properties of Cashew Nuts - Nathakaranakule, Adisak; Prachayawarakorn, Somkiat (Agriculture and Natural Resources, 1998)
Physical properties of kernel and whole shell of cashew nuts; specific heat, density, equilibrium moisture content and thin layer drying equation, were determined. The specific heat and density of both types of cashew nut depend linearly on their moisture content. For the experiments of equilibrium moisture content, the static method was used in the range of 50°C , 62°C and 74°C and relative humidity in the range of 10.96 - 88.46 percent. For the kernel, equilibrium moisture content models based on the equations of Henderson and Modified Henderson were accurate to predict the equilibrium moisture content. While the equilibrium moisture content models based on Henderson and Chung and Pfost equations were suitable for the whole shell. The experiments of the thin-layer drying were performed at the temperature of 60°C, 80°C and 100°C, the air velocity of 2.5 and 3 m/s, and the initial moisture content between 17 - 25 %db. The results showed that the effect of initial moisture content and air velocity were negligible, but the effect of temperature was significant. By considering the shape of cashew nut to be cylindrical, the semi-empirical relation was developed by crossing the equation for infinite cylinder and infinite slab. Then it was found that the thin layer drying equation and the effective diffusivity equation were in the exponential form.